2004
DOI: 10.1196/annals.1320.005
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine Replacement in End‐Stage Renal Disease and Hemodialysis

Abstract: In patients with chronic renal failure, not yet undergoing hemodialysis (HD), plasma acylcarnitines accumulate in part due to a decreased renal clearance of esterified carnitine moieties. In these patients, a high acylcarnitine/free-carnitine ratio is usually found in plasma. Patients undergoing maintenance HD, usually present with plasma carnitine insufficiency, due to accumulation of metabolic intermediates combined with impaired carnitine biosynthesis, reduced protein intake and increased removal via HD. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 65 publications
0
39
0
5
Order By: Relevance
“…The levels of acylcarnitines are increased in plasma of patients with several inherited metabolic diseases. In these cases, the endogenous pool of carnitine becomes insufficient to cope with the required acyl transfer, and the plasma AC/FC ratio increases (10). The increase in AC/FC ratio reflects changes in the intramitochondrial equilibrium between acylCoA and free CoA (7,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of acylcarnitines are increased in plasma of patients with several inherited metabolic diseases. In these cases, the endogenous pool of carnitine becomes insufficient to cope with the required acyl transfer, and the plasma AC/FC ratio increases (10). The increase in AC/FC ratio reflects changes in the intramitochondrial equilibrium between acylCoA and free CoA (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…CrAT plays an important role in maintaining carnitine metabolism (10). Therefore, we next determined total carnitine and free carnitine levels in the peripheral lung of shunt and control lambs.…”
Section: Increased Nitration Decreases Crat Activity In Shunt Lambsmentioning
confidence: 99%
“…Furthermore, LC may reduce insulin resistance and chronic inflammation. [11] We have previously found that CRP levels may decrease by LC treatment. Additionally, there was a significant benefit of LC on transferrin, total protein, and albumin levels of the hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the stabilizing effect of L -carnitine on the erythrocyte membrane and by improvement in physical fitness secondary to the improved skeletal muscle metabolism with a subsequent decrease in blood transfusion requirement [41]. Moreover, the decrease in blood requirements could be secondary to increased responsiveness to erythropoietin which has been attributed to the effect of L -carnitine on erythropoietin-resistant anemia in hemodialysis patients [42]. Unfortunately, fetal hemoglobin or hemolysis markers (which might have shed some light on the mechanism involved in this decrease in need for transfusions) were not assessed at the end of the trial as this was not within the scope of this study.…”
Section: Discussionmentioning
confidence: 99%